2021
DOI: 10.1083/jcb.202104107
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical competition alters the cellular interpretation of an endogenous genetic program

Abstract: The intrinsic genetic program of a cell is not sufficient to explain all of the cell’s activities. External mechanical stimuli are increasingly recognized as determinants of cell behavior. In the epithelial folding event that constitutes the beginning of gastrulation in Drosophila, the genetic program of the future mesoderm leads to the establishment of a contractile actomyosin network that triggers apical constriction of cells and thereby tissue folding. However, some cells do not constrict but instead stretc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 86 publications
3
38
0
Order By: Relevance
“…1 g). This corroborates previous experimental evidence and quantitative analysis showing that cells further away from the midline increase their surface area during furrow formation 4 , 10 , 33 , 58 , 61 , 62 . This spatial strain pattern is reproduced by our computational model (Fig.…”
Section: Resultssupporting
confidence: 92%
“…1 g). This corroborates previous experimental evidence and quantitative analysis showing that cells further away from the midline increase their surface area during furrow formation 4 , 10 , 33 , 58 , 61 , 62 . This spatial strain pattern is reproduced by our computational model (Fig.…”
Section: Resultssupporting
confidence: 92%
“…When most of the transcription sites in the ventral region are triggered over time, the differences in mRNA production diminish. Indeed, monitoring apical Myosin II recruitment showed that lateral mesodermal cells eventually recruit similar levels to the ventral-most cells ( Bhide et al, 2021 ). For optimal function, the probability of transcription activation should be high enough to prime a significant number of TSs and yet not plateau within the critical time window.…”
Section: Discussionmentioning
confidence: 99%
“…2a-b,e-f ). During early VFF, cells with mesodermal fate (marked by the expression of the transcription factor Snail) located on the ventral side of the embryo undergo complex changes in cell geometry that will enable the complete invagination of these cells in ~15min 28 ( Fig. 2a,b ).…”
mentioning
confidence: 99%